Alternative approach on design and construction of low-cost houses proposed by Bangkok Metropolitan Administration - Khan, Sardar; Pichai Nimityongskul; Sheng, Yap Kioe; Varma, Mahesh; Ministry of Defence Government of Pakistan (Bangkok : Asian Institute of Technology, 1990)
A pre fabricated low-cost project was undertaken by the Bangkok Metropolitan n Administration (BMA) , in order to respond to the housing needs of the low-income families in the a rea. BMA pro posed four types of low- cost houses which could be built by the people themselves . Evaluation studies of the BMA houses indicated that the houses designs have many structura1 and materials defects and accommodation deficiencies and as a result , the project has not bee n particularly successful . This study was under taken to provide alternative structural designs for the BMA houses. For this purpose the existing designs , materials and labor availability, and construction techniques in t he area we r e studied in detail. Alternative designs in corpora ting new materials, as well as improved structural and architectural designs have been proposed for the BMA houses. The alternative designs are in three types for three low- income groups but the type intended for the lowest - income groups can readi1y be expanded and converted to the next type without any dismantling . On comp a ring the alternative designs with the existing designs for BMA houses, the former are found to be more superior to the latter interns of structural strength, materials durability and appearance beside bein glower in cost. Additionally the pre - fabricated ferrocement panelling system adopted for the BMA houses can successfully be used in other low-cost buildings elsewhere in Thailand or in other developing countries. Further the alternative designs have the potential to be further improved to match conventional luxurious houses.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1990
Keywords: Housing -- Thailand -- Bangkok; House construction -- Thailand -- Bangkok